Chromatographic Analysis of a Cytokinin from Tissue Cultures of Crown-Gall - Tegley, John R. (1971)
Extracts from tissue cultures of crown-gall from Parthenocissus tricuspidata (Sieb. and Zucc.) Planch. exhibited cell division activity in the soybean cytokinin assay. The chromatographic migration of one component, responsible for most of the activity, is similar to that of zeatin ribonucleoside. In addition, acid hydrolysis of the active region taken from chromatograms and of an eluate from a cation-exchange resin column resulted in the production of an active free-base-like derivative. Since the derivative and the parent compound lose activity after KMnO(4) treatment, they are believed to possess an unsaturated constituent essential for biological activity. The major active factor present in crown-gall from Parthenocissus tricuspidata is therefore distinct from the nicotinamide derivative reported to be present in Vinca rosea L. tumor cells.